Adsorption of Cu2+, Zn2+, and Ni2+ ions onto the adsorbent prepared from fluid catalytic cracking spent catalyst fines and diatomite - Zheng, Shu-Qin (Array, 2019)
An adsorbent prepared from fluid catalytic cracking (FCC) spent catalyst fines and diatomite, and its adsorption of Cu2+, Zn2+, and Ni2+ ions were investigated. The adsorbent was characterized by XRD, SEM, and N2 adsorption-desorption techniques. The results showed that the specific surface area and pore volume of adsorbent increased with the increase in FCC spent catalyst fines. The influence factors on the adsorption of the adsorbents were studied. The suitable adsorption conditions were: pH value of 5.0, ratio of solid to liquid of 1 : 600 (g:ml), adsorption time of 4 h, room temperature. The adsorption of metal ions varied with the type of metal cations. The adsorption isotherms suggested that the sequence of the adsorption efficiency was Cu2+ >Zn2+ >Ni2+. The amount of Cu2+, Zn2+, and Ni2+ metal ion adsorbed onto the adsorbent was 49.17 mg g–1, 46.83 mg g–1, and 35.72 mg g–1, respectively. The adsorption data of Cu2+, Zn2+, and Ni2+ ions fitted well with the Freundlich adsorption isotherm model.